2017
DOI: 10.5147/pggb.v1i3.153
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Seed Amino Acid Content QTL Detected Using the Universal Soy Linkage Panel 1.0 with 1,536 SNPs

Abstract: Soybean [Glycine max (L.) Merr.] is the primary source of meal used in animal feed in the U.S. However, few studies have been conducted to evaluate genomic regions controlling amino acid composition is soybean. Designing soybean seed compositions that will benefit animal production is essential. The objective of this study was to identify genomic regions controlling essential and non-essential amino acid composition in soybean seed proteins. To achieve this objective, 282 F5:9 recombinant inbred lines (RILs) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 25 publications
1
21
1
Order By: Relevance
“…Stability of Pi content was calculated using ANOVA and least square means estimation, similar to the procedure described by Fallen et al (2013) and by Mellinger (2012). To estimate the stability of Pi content across locations, the REG procedure was used in SAS 9.3.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stability of Pi content was calculated using ANOVA and least square means estimation, similar to the procedure described by Fallen et al (2013) and by Mellinger (2012). To estimate the stability of Pi content across locations, the REG procedure was used in SAS 9.3.…”
Section: Methodsmentioning
confidence: 99%
“…Stability of Pi content was calculated using ANOVA and least square means estimation, similar to the procedure described by Fallen et al (2013) and by Mellinger (2012). To estimate the stability of Pi content across locations, the REG significant differences between the LP lines and the USDA checks for seed yield, lodging, height, field emergence, plant maturity, and seed weight; (ii) to compare the seed quality traits of 56CX-1273 and 56CX-1283 to cultivars Osage and 5002T by testing the null hypothesis of no significant differences between the LP lines and the USDA checks for seed protein, oil, meal protein, seed amino acid levels, and seed fatty acid components; and (iii) to evaluate the environmental stability of the LP trait in LP lines 56CX-1273 and 56CX-1283 when grown in six southern US environments of the 2013 United Soybean Board (USB) MG V Quality Traits Test.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost 20 years ago, the economic benefit of improved essential amino acid content was estimated to be ~$5 per ton per 10% increase of any of the above-mentioned amino acids [105], and today the benefit could be even bigger. The knowledge of the molecular mechanism of amino acid biosynthesis in soybean was mainly limited to genetic mapping [106,107], but recent studies have enhanced our understating of amino acid genetic architecture in soybean. For example, Vaughn et al [108] conducted GWAS for methionine, threonine, cysteine and lysine and identified multiple loci associated with multiple amino acids across different populations not reported previously.…”
Section: Protein Content and Amino Acid Compositionmentioning
confidence: 99%
“…Molecular breeding techniques have recently improved the understanding of amino acid genomic regulation. Multiple quantitative trait loci (QTL) studies have been performed to identify genomic regions that control amino acids levels in soybean seed [60][61][62][63][64]. A myriad of QTL's were found to create amino acid phenotypic variation.…”
Section: Breeding Effortsmentioning
confidence: 99%